White matter integrity differences in 2-year-old children treated with ECMO: a diffusion-weighted imaging study : research report - Ruttorf, Michaela; Filip, Julia; Schaible, Thomas; Weis, Meike; Zöllner, Frank G. (European journal of neuroscience, 2025)
School-aged and adolescent survivors of neonatal extracorporeal membrane oxygenation (ECMO) treatment still suffer from neurodevelopmental delays such as verbal, visuo-spatial and working memory problems, motor dysfunction and sensorineural hearing loss, respectively, later in life, which is well-documented by neuropsychological testing within follow-up programs. In this study, we demonstrate that diffusion-weighted imaging (DWI) in 2-year-old survivors of neonatal ECMO treatment reveals white matter (WM) alterations in brain regions related to neurodevelopmental outcome seen later in life. From the DWI data of 56 children, fractional anisotropy (FA), first fibre partial volume fraction estimate (F1), radial diffusivity (RD) and mean diffusivity (MD) are calculated and compared using tract-based spatial statistics adapted to a paediatric brain atlas. Significant differences in FA, F1, RD and MD between the no-ECMO and ECMO groups are seen in major WM tracts. Additionally, we examine individual diffusion measures by looking at 50 regions supplied with the paediatric brain atlas. We find the following regions to have significantly different means in the no-ECMO compared with the ECMO group matching reports of neuropsychological delays found in behavioural tests: left anterior corona radiata, left anterior limb of internal capsule, left anterior commissure, left and right corpus callosum (genu, body and splenium), left and right crus of fornix and left tapetum. Analysing diffusion measures at an early stage of life serves as a good tool to detect structural WM changes in survivors of neonatal ECMO treatment. Compared with neuropsychological testing, DWI does not depend on the child's active participation.
Erstmals veröffentlicht: 17. Februar 2025
Gesehen am 17.07.2025